Aeroelastic Tailoring Of Woven Cantilevered Glass-Epoxy Plate-Like Aircraft Wing - Abang Haji Abdul Majid, Dayang Laila (2008)

(untitled)
The application of uni-directional composites in aeroelastic tailoring has long been established due to their highly directional properties. However, the use of woven, bi-directional textile composite in this area is practically nil due to their lower strength and stiffness, although this class of material is generally cheaper and more conforming. Therefore, the current work presents a new prospect for this type of material in the aeroelastic tailoring of aircraft wings. The aeroelastic flutter and divergence behaviour of rectangular, woven glass/epoxy cantilevered plates with varying amount of bending and torsion stiffness coupling is investigated in subsonic flow. To do so, a range of tailored plate configurations with various stacking sequence having 6-plies thickness were considered. The ply orientation was varied from -450 to 450 to provide the widest range of negative and positive bend-twist coupling. Test plates without stiffness coupling were first constructed and subjected to static and dynamic testing in order to characterize the elastic and dynamic behaviour of the plate. Secondly, tailored configurations with varying stiffness coupling were fabricated and tested for flutter in wind tunnel tests. Numerical analyses were also conducted using MSc.Nastran structural analysis in conjunction with ZAERO’s flutter program to verify the mechanical and dynamic properties as well as predict the occurrence of flutter and divergence. Results from the extensive experimental and computational works had successfully shown that flutter speed can be optimized by tailoring the woven composite laminates. It was found that the torsional stiffness and bend-twist coupling play a major role in the aeroelastic behaviour of the woven laminate as compared to the bending stiffness. The bend-twist flutter that occurred was dominated by the torsion mode, thus explained the significant effect it has on the flutter speed. The numerical calculations predicted a 37% improvement whereas the experimental results are more understated at 29%. This improvement is remarkable considering that the configurations are symmetric. Both agreed well in terms of the optimized configuration that gave the maximum flutter speed. The flutter frequency and flutter mode shape was shown to be highly dependent on the coupled structural modes. In addition, divergence occurred when the plate-like wing is swept forward.